A Novel Combine Between the Opinion Weight Criteria Method (OWCM) and FDOSM - Hind Alaa Abdul-Kareem; Mahmood Maher Salih (IEEE Access)
Fuzzy decision by opinion score method (FDOSM) is one of the latest methods in multi criteria decision making area using to select the best alternative from a set of alternatives. FDOSM addressed many problems in other MCDM methods. However, FDOSM suffered from the implicit weight and needs to extract wright to explain the expert weight. Opinion weight criteria method (OWCM) is the latest method was developed to extracting weight for the evaluation criteria. In this article present a novel combine between the OWCM and FDOSM. The methodology of the article contains the four phases, phase one necessary to extract the research gap. Phase two is present the novel combine between OWCM and FDOSM. The new combination applied in network case study was presented in phase three. Finally, in phase four present a comparative analysis for the proposed combine and the basic FDOSM. The final result and the comparative analysis present the effect of the extract weight, and prove that FDOSM needs extracting weight to make more accurate decision.